Nanoscale Aspects of Phase Transitions in Copper Based Shape Memory Alloys - Adiguzel, O. (Springer, 2015)
Shape memory alloys take place in a class of smart materials by exhibiting a peculiar property called shape memory effect. This property is characterized by the recoverability of desired shape on the material at different conditions. Shape memory effect is based on a solid state phase transition, martensitic transformation, which occurs in the materials on cooling from high temperature and characterized by changes in the crystal structure of the material at nano-level rather than micrometer. Copper based alloys exhibit this property in metastable beta-phase field, which have bcc-based structures at high temperature. These structures martensitically undergo the non-conventional structures on cooling from high temperature parent phase region. The product phase has the unusual complex structures called long period layered structures such as 3R, 9R or 18R depending on the stacking sequences on the close-packed planes of the ordered lattice.
NATO Advanced Research Workshop on Nanotechnology in the Security Systems -- SEP 29-OCT 03, 2013 -- Yalta, UKRAINE
Keywords: Martensite